1987
DOI: 10.1016/0014-5793(87)81019-0
|View full text |Cite
|
Sign up to set email alerts
|

GTP‐dependent ADP‐ribosylation of a 22 kDa protein in the endoplasmic reticulum membrane

Abstract: Treatment of salt-stripped rough microsomal membranes from pancreas or liver with NAD and cholera toxin in the presence of GTP yields an ADP-ribosylated non-ribosomal 22 kDa protein. Membranes containing the modified protein are less active in the co-translational processing of secretory preproteins translated from isolated mRNA in a reticuloeyte translation system, but signal peptidase activity is unchanged, suggesting that the 22 kDa protein is involved in the targetting or translocation of secretory protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Although we cannot exclude the possibility that the 22 kDa GTP-binding proteins that we detect in rough microsomes are due to contamination by plasma-membrane derivatives, we consider this unlikely, because of the low amounts of plasmamembrane marker enzyme in this preparation (see Table 1) and because the specific 23.5 kDa GTP-binding proteins with pl values extending from 6.7 to 6.2 found in the plasma-membrane fraction are absent from the roughmicrosomal fraction. The 22 kDa GTP-binding proteins that we detect in rough microsomes may correspond to the 22 kDa ADP-ribosylated protein previously described in purified RER membranes by Robinson & Austen (1987). Purified rat liver rough microsomes contain two specific groups of GTP-binding proteins.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Although we cannot exclude the possibility that the 22 kDa GTP-binding proteins that we detect in rough microsomes are due to contamination by plasma-membrane derivatives, we consider this unlikely, because of the low amounts of plasmamembrane marker enzyme in this preparation (see Table 1) and because the specific 23.5 kDa GTP-binding proteins with pl values extending from 6.7 to 6.2 found in the plasma-membrane fraction are absent from the roughmicrosomal fraction. The 22 kDa GTP-binding proteins that we detect in rough microsomes may correspond to the 22 kDa ADP-ribosylated protein previously described in purified RER membranes by Robinson & Austen (1987). Purified rat liver rough microsomes contain two specific groups of GTP-binding proteins.…”
Section: Discussionsupporting
confidence: 66%
“…Segev et al (1988) suggested that GTP-binding proteins may be present at other stages of the secretion pathway in mammalian cells as well as in yeast. Consistent with this suggestion are data indicative of similar proteins in the Golgi apparatus (Melanron et al, 1987;Segev et al, 1988), in transition vesicles (Beckers & Balch, 1989) and rough endoplasmic reticulum (RER) (Godelaine & Beaufay, 1987; Robinson & Austen, 1987;Audigier et al, 1988).…”
Section: Introductionmentioning
confidence: 74%